NADP-dependent enzymes are involved in response to salt and hypoosmotic stress in cucumber plants - Hýsková, Veronika; Plisková, Veronika; Červený, Václav; Ryšlavá, Helena (General physiology and biophysics, 2017)
Salt stress is one of the most damaging plant stressors, whereas hypoosmotic stress is not considered to be a dangerous type of stress in plants and has been less extensively studied. This study was performed to compare the metabolism of cucumber plants grown in soil with plants transferred to distilled water and to a 100 mM NaCl solution. Even though hypoosmotic stress caused by distilled water did not cause such significant changes in the relative water content, Na+/K+ ratio and Rubisco content as those caused by salt stress, it was accompanied by more pronounced changes in the specific activities of NADP-dependent enzymes. After 3 days, the specific activities of NADP-isocitrate dehydrogenase, glucose-6-phosphate dehydrogenase, NADP-malic enzyme and non-phosphorylating glyceraldehyde-3-phosphate dehydrogenase in leaves were highest under hypoosmotic stress, and lowest in plants grown in soil. In roots, salt stress caused a decrease in the specific activities of major NADP-enzymes. However, at the beginning of salt stress, NADP-galactose-1-dehydrogenase and ribose-1-dehydrogenase were involved in a plant defense response in both roots and leaves. Therefore, the enhanced demands of NADPH in stress can be replenished by a wide range of NADP-dependent enzymes.
Keywords: Multienzyme Complexes; Osmotic Pressure; Salt Tolerance; Stress, Physiological; osmotický tlak; multienzymové komplexy; Sodium Chloride; semenáček; tolerance k soli; NADP; fyziologický stres; Seedlings; chlorid sodný; Cucumis sativus